Electrotechnical systems : simulation with Simulink® and SimPowerSystems - Perelʹmuter, V. M. (Viktor Moiseevich) (CRC Press, Taylor & Francis Group, 2013)
Filling a gap in the literature, Electrotechnical Systems: Simulation with Simulink® and SimPowerSystemsTM explains how to simulate complicated electrical systems more easily using SimPowerSystemsTM blocks. It gives a comprehensive overview of the powerful SimPowerSystems toolbox and demonstrates how it can be used to create and investigate models of both classic and modern electrotechnical systems. Build from Circuit Elements and Blocks to System ModelsBuilding from simple to more complex topics, the book helps readers better understand the principles, features, and detailed functions of various.